Mental Health Training Programs for Community Pharmacists in Low Middle-income Countries: A Systematic Review (Bangladesh Journal of Medical Science, 2023)
Objective: This review aimed to explore the potential approachto continuing education and training the community pharmacists to equip them to support mental health consumers in lowmiddle- income countries.Materials and Methods: A systematic search strategy was conducted using Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Search terms related to mental health, training program, and community pharmacist were used in three major databases (i.e.,PubMed, Science Direct, and Scopus), retrieving a total of 5575 articles. Ten studies met the inclusion criteria.Results and Discussion: There was evidence that shortduration delivery and non-direct contact training with patient diagnosed with mental illness (consumer educator or peer-level-educator) have the same effect as long training delivery and direct contact intervention. Consumer educator or peer-level-educator in mental health training programs are key factors to improved mental health knowledge, attitudes, and pharmaceutical care service of community pharmacists.Conclusion: Flexible nondirected delivery methods using video footage of expert and mental health patients were preferred for a low-cost program accessible to a large community pharmacy workforce which can be applicable in developing countries. However, there is an urgent need for further studies to clarify actual changes in the attitude of and daily service by pharmacists after participating in a mental health training program.Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page : 284-296